Metal Coordination: Improving Metal Adsorption on Triethylenetetramine (TETA) Functionalized SBA‐15 Mesoporous Silica Using Potentiometry, EPR and ssNMR (Adv. Mater. Interfaces 15/2020). Issue 15 (6th August 2020) - Lachowicz, Joanna Izabela; Emwas, Abdul‐Hamid; Delpiano, Giulia Rossella; Salis, Andrea; Piludu, Marco; Jaremko, Lukasz; Jaremko, Mariusz
Abstract : Metal ion chelators combined with nanostructure materials proved effective in the treatment and diagnosis of human diseases. Combine potentiometry, EPR and NMR techniques determine ligand content, metal complex stability constants and competition between metallodrugs and endogenous molecules. More details can be found in article number 2000544 by Joanna Izabela Lachowicz, Mariusz Jaremko, and co‐workers.